Clinical pharmacology of alemtuzumab, an anti-CD52 immunomodulator, in multiple sclerosis. (1st October 2018) - Li, Z; Richards, S; Surks, H K; Jacobs, A; Panzara, M A
Summary: Alemtuzumab, a humanized anti-CD52 monoclonal antibody, is approved for treatment of relapsing multiple sclerosis (MS). In the Phase II/III trials, patients received 12 or 24 mg/day of alemtuzumab in two treatment courses (5 days for course 1 and 3 days for course 2), 12 months apart. Serum concentrations of alemtuzumab peaked on the last day of dosing in each course and mostly fell below the limit of quantitation by day 30. Alemtuzumab rapidly depleted circulating T and B lymphocytes, with the lowest observed values occurring within days. Lymphocytes repopulated over time, with B cell recovery usually complete within 6 months. T lymphocytes recovered more slowly and generally did not return to baseline by 12 months post-treatment. Approximately 40 and 80% of patients had total lymphocyte counts, reaching the lower limit of normal by 6 and 12 months after each course, respectively. The clearance of alemtuzumab is dependent on circulating lymphocyte count. A majority of treated patients tested positive for anti-alemtuzumab antibodies, including inhibitory antibodies, during the 2-year studies, and a higher proportion of patients tested positive in course 2 than in course 1. The presence of anti-alemtuzumab antibody appeared to be associated with slower clearance of alemtuzumab from the circulation but had no impact on the pharmacodynamics. No effects of age, race or gender on the pharmacokinetics or pharmacodynamics were observed. Together, the pharmacokinetics, pharmacodynamics and immunogenicity results support the continued development and use of alemtuzumab for the treatment of MS, and probably explain its sustained effects beyond the dosing interval. Graphical Abstract: